Pemberdayaan Perempuan Melalui Kerajinan Batik di Desa Bentarsari Kecamatan Salem Kabupaten Brebes - Oktopiah, Emas Oti; Mutmainah, Nur Fitri (Journal of Economics, Bussiness and Management Issues, 2024)
Women empowerment is a form of empowerment carried out for women in order to achieve a decent life. Empowerment is carried out in the form of women's awareness to develop and is used as efforts in overcoming women's underdevelopment. The empowerment programme in Bentarsari Village (Mawar Batik) aims to improve living standards and alleviate poverty. The study is to analyze how women's empowerment through batik handicrafts is in improving the economy. It also identifies the factors influencing the empowerment programme in Bentarsari Village. The study employed descriptive qualitative approach with data collection techniques through observation, interviews and documentation. The data obtained were analysed by using data reduction, data presentation, and conclusion drawing. The results showed the success of women empowerment in Bentarsari Village, Salem District in the batik craft programme. The supporting and inhibiting factors which influence the success are the support of husbands and the willingness to change from the community so that the skills possessed are hereditary and good communication between group members and group leaders.